Toxicity of Brazilian Medicinal Plant Extracts on Macrobrachium Amazonicum - Gemaque, Tainára Cunha; Silva, Sérgio Rodrigues da; Melo, Daniele Salgueiro de; Costa, Daniel Pereira da; Filho, Kleber Campos Miranda (Journal of Agricultural Studies, 2021)
Medicinal plants from Amazon have been commercialized for decades, but few scientific studies prove their effectiveness and safety in use in aquaculture activities. The objective of the present study was to use the Amazon river prawn Macrobrachium amazonicum to predict the toxicity of the natural extracts of nine medicinal plants viz pariri Arrabidaea chica, muirapuama Ptychopetalum olacoides, anauerá Licania macrophylla, barbatimão Ouratea hexasperma, faveira Vatairea guianensis, sacaca Croton cajucara, jacareúba Calophyllum brasilliense, pau d’arco Tabebuia sp. and verônica Dalbergia subcymosa, in concentrations of 1, 10, 100, 500 and 1000 µg/mL. The media was prepared in 0.5% dimethyl sulfoxide (DMSO) diluted with water. Ten post-larvae (0.5 ± 0.1 g) were added to each triplicate and, after 24 h, the mortalities were evaluated, with the results of median lethal concentration expressed as LC50-24h using the Probit statistical method. To obtain the concentrations of a common bioactive compound of plant extracts, the concentrations of flavonoids were analyzed using a methodology based on the formation of chromophores. The results of acute toxicity indicate variability in the toxic effects of medicinal plants, taking into account the concentration of total flavonoids, with the least toxic Tabebuia sp. (LC50 = 758.31 µg/mL) and the most toxic C. cajucara and V. guianensis (LC50 = 72.16 and 75.23 µg/mL), respectively. The extracts demonstrated lethality against M. amazonicum, which predicts toxicity and warns of its use them as herbal medicines. More studies must be carried out to determine other bioactive compounds in the plant extracts used since there is an unparalleled availability of chemical diversity.